Digital microscopy - Sluder, Greenfield, editor; Wolf, D. E. (David E.), editor (San Diego, CA Academic Press is an imprint of Elsevier, 2013)
The previous edition of this book marked the shift in technology from video to digital camera use with microscope use in biological science. This new edition presents some of the optical fundamentals needed to provide a quality image to the digital camera. Specifically, it covers the fundamental geometric optics of finite- and infinity-corrected microscopes, develops the concepts of physical optics and Abbe’s theory of image formation, presents the principles of Kohler illumination, and finally reviews the fundamentals of fluorescence and fluorescence microscopy. The second group of chapters deals with digital and video fundamentals: how digital and video cameras work, how to coordinate cameras with microscopes, how to deal with digital data, the fundamentals of image processing, and low light level cameras. The third group of chapters address some specialized areas of microscopy that allow sophisticated measurements of events in living cells that are below the optical limits of resolution.--Provided by publisher.
Microscope basics / Greenfield Sluder, Joshua J. Nordberg -- The optics of microscopic image foundation / David E. Wolf -- Proper alignment of the microscope / Rudi Rottenfusser -- Fundamentals of fluorescence and fluorescence microscopy / David E. Wolf -- Fluorescent protein applications in microscopy / Whitney L. Johnson, Aaron F. Straight -- Live-cell fluorescence imaging / Jennifer C. Waters -- Practical aspects of adjusting digital cameras / Joshua J. Nordberg, Greenfield Sluder -- Cameras for digital microscopy / Kenneth R. Spring -- A high-resolution multimode digital microscope system / Edward D. Salmon, Sidney L. Shaw, Jennifer C. Waters, Clare M. Waterman-Storer, Paul S. Maddox, Elaine Yeh, Kerry Bloom -- Electronic cameras for low-light microscopy / Ivan Rasnik, Todd French, Ken Jacobson, Keith Berland -- Camera technologies for low light imaging : overview and relative advantages / Butch Moomaw -- Post-processing for statistical image analysis in light microscopy / Richard A. Cardullo, Edward H. Hinchcliffe -- 65,000 shades of grey : use of digital image files in light microscopy / Sidney L. Shaw, Edward H. Hinchcliffe -- Quantitative analysis of digital microscope images / David E. Wolf, Champika Samarasekera, Jason R. Swedlow -- Evaluating optical aberrations using fluorescent microspheres : methods, analysis, and corrective actions / Paul C. Goodwin -- Ratio imaging : practical considerations in measuring intracellular CA2+ and pH in living cells / Nathan O'Connor, Randi B. Silver -- Quantitative fluorescence microscopy and image deconvolution / Jason R. Swedlow -- Practical aspects of quantitative confocal microscopy / John M. Murray -- Theoretical principles and practical considerations for fluorescence resonance energy transfer microscopy / Richard A. Cardullo -- Fluorescence lifetime imaging microscopy for quantitative biological imaging / Leng-Chun Chen, William R. Lloyd, III, Ching-Wei Chang, Dhruv Sud, Mary-Ann Mycek -- Fluorescence correlation spectroscopy : molecular complexing in solution and in living cells / Dylan A. Bulseco, David E. Wolf -- Breaking the resolution limit in light microscopy / Rainer Heintzmann, Gabriella Ficz -- Circumventing photodamage in live-cell microscopy / Valentin Magidson, Alexey Khodjakov -- A user's guide to localization-based super-resolution fluorescence imaging / Graham T. Dempsey -- Quantitative ratiometric imaging of FRET-biosensors in living cells / Désirée Spiering, Jose Javier Bravo-Cordero, Yasmin Moshfegh, Veronika Miskolci, Louis Hodgson -- Tip-enhanced raman spectroscopy for the base interrogation of DNA / Noah
Includes bibliographical references and index.
Keywords: Video microscopy; Microscopy; Image processing -- Digital techniques; Electronic books